2021
DOI: 10.3389/fcvm.2021.638011
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning in Diagnosis of COVID-19 Through X-Ray and CT Images: A Scoping Review

Abstract: Coronavirus disease, first detected in late 2019 (COVID-19), has spread fast throughout the world, leading to high mortality. This condition can be diagnosed using RT-PCR technique on nasopharyngeal and throat swabs with sensitivity values ranging from 30 to 70%. However, chest CT scans and X-ray images have been reported to have sensitivity values of 98 and 69%, respectively. The application of machine learning methods on CT and X-ray images has facilitated the accurate diagnosis of COVID-19. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 119 publications
1
41
0
2
Order By: Relevance
“…Investigators have developed many models to detect COVID-19 during the past two years and have shown that there is a role for AI in detecting COVID-19 [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 277 , 278 , 279 , 280 , 281 ]. The 184 technical papers reviewed in this study provide up-to-date knowledge on the usage of AI techniques in detecting COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have developed many models to detect COVID-19 during the past two years and have shown that there is a role for AI in detecting COVID-19 [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 277 , 278 , 279 , 280 , 281 ]. The 184 technical papers reviewed in this study provide up-to-date knowledge on the usage of AI techniques in detecting COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the wide accessibility of CT scanners makes this task quicker. Adding to this, Machine learning (ML) and Deep learning (DL) methods are evolving rapidly that can lessen the workload of the medical experts by providing an automatic interpretation from a huge data sets [7] [10] , [39] . Zhao et al [11] developed a transfer learned DenseNet model for the classification of CT scan images into COVID + ve and Normal categories.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as random rotations and translations of the training images were used by Alazab et al to artificially increase the size of their dataset from 98 to 1,000 training images and achieve competitive COVID-19 detection results [8]. Many papers report validation accuracies of over 95% [9].…”
Section: Introductionmentioning
confidence: 99%